Power, Piety, and Patronage in Late Medieval Queenship - Silleras-Fernandez, N. author. aut Link
XX, 250 p.
Keywords: Based on an exhaustive and varied study of predominantly unpublished archival material as well as a variety of literary and non-literary sources, this book investigates the relation between patronage, piety and politics in the life and career of one Late Medieval Spain's most intriguing female personalities, Maria De Luna.